2009
DOI: 10.1007/s10735-009-9230-5
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas-specific protein disulfide isomerase has a cell type-specific expression in various mouse tissues and is absent in human pancreatic adenocarcinoma cells: implications for its functions

Abstract: Members of the protein disulfide isomerase (PDI) family play a critical role in catalyzing the formation of disulfide bonds in secretory proteins, and most of these enzymes have a wide tissue distribution. However, the pancreas-specific PDI homolog was previously suggested to be exclusively expressed in the pancreas (thus commonly referred to as PDIp). In the present study, we found that PDIp was also highly expressed in several other tissues in mice, including the stomach, cecum, ileum, adrenal glands, epidid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Following this observation, we also showed that the accumulation of E 2 in the pancreas is largely attributable to PDIp [pancreas-specific PDI (protein disulfide isomerase)], which has a high capacity for binding E 2 in vitro and in vivo and can also slow down E 2 metabolism in vitro. PDIp was previously reported to be a protein-folding catalyst [25][26][27], predominantly localized in the endoplasmic reticulum [28] and selectively expressed at high levels in pancreatic acinar cells [25,[28][29][30][31]. The results of the present study indicate that besides serving as a proteinfolding catalyst, PDIp may also have other biological functions through modulating pancreatic tissue levels and the metabolism of endogenous oestrogens.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Following this observation, we also showed that the accumulation of E 2 in the pancreas is largely attributable to PDIp [pancreas-specific PDI (protein disulfide isomerase)], which has a high capacity for binding E 2 in vitro and in vivo and can also slow down E 2 metabolism in vitro. PDIp was previously reported to be a protein-folding catalyst [25][26][27], predominantly localized in the endoplasmic reticulum [28] and selectively expressed at high levels in pancreatic acinar cells [25,[28][29][30][31]. The results of the present study indicate that besides serving as a proteinfolding catalyst, PDIp may also have other biological functions through modulating pancreatic tissue levels and the metabolism of endogenous oestrogens.…”
Section: Introductionsupporting
confidence: 62%
“…Secondly, although PDI is abundantly expressed in many tissues [28,34], PDIp is highly and selectively expressed in the pancreas, at an estimated concentration of up to 0.5 % of the total cellular proteins [25,28]. Thirdly, the molecular sizes of PDI and PDIp appear to be comparable with the sizes seen at the SEC elution volumes for fractions A7 and A8 (Figure 2A and Supplementary Figure S2).…”
Section: Identification Of Pdip As the Most Abundant E 2 -Binding Promentioning
confidence: 86%
See 2 more Smart Citations
“…Pdip expression level was highest in the corpus and appeared to be localized to gastric chief cells (16).…”
Section: Digestion and Absorptionmentioning
confidence: 97%